Answer:
87.47 cm
Step-by-step explanation:
112-24.53 is 87.47
ok so first we would do the function d(x) = 3(8)+2
which when solved turns out to be 26
we would then do the function h(x) = 2(26) +7
which when solved turns out to be 59
so he would need 59 dollars for the donuts
Answer:
Step-by-step explanation:
y - z+6
35+25=60
y=60
If you add the opposite side values of the triangle (not the one touching the y), you get the value of y). 35+25=y
This works because y+x= 180 and the three angles of a triangle add to 180.
If the sequence is like this, you actually don’t have to
formulate a formula. You just have to formulate a principle. You just have to
remember that when n is an odd number, the value would always be 1. If the n is
an even number, the value would always be 0.